2011
DOI: 10.1016/j.breast.2011.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer subtypes and outcomes of central nervous system metastases

Abstract: Central nervous system (CNS) metastases are detected in up to one third of patients with advanced breast cancer, but their incidence and outcomes by breast cancer subtypes are not precisely documented. Herein, we retrospectively analyzed clinicopathologic data of 259 breast cancer patients with CNS metastases to evaluate the association between breast cancer subtypes and CNS metastasis. The patient groups were classified according to their hormone receptor status and HER-2 expression. Median follow-up time amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
3
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 37 publications
3
54
3
7
Order By: Relevance
“…In the present study, the median OS after brain metastasis was approximately 10 months and better than according to other published data [4,12,13,14]. We think that this may be due to several reasons.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In the present study, the median OS after brain metastasis was approximately 10 months and better than according to other published data [4,12,13,14]. We think that this may be due to several reasons.…”
Section: Discussioncontrasting
confidence: 54%
“…Survival was reported to be about 1.5 years in HER2-positive patients with brain metastasis treated with targeted treatment [16,17]. While targeted treatment is employed in 70% of HER2-positive patients (HER2-overexpressing and luminal B) in our study, it was employed in 36% [12] and 47% in studies which reported lower survival [14]. In line with this and previous studies, the triple negative subgroup had lower survival rates than the other subgroups in our study [4,12,13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Younger age (Tsukada et al, 1983;Carey et al, 2004), advanced stage (Carey et al, 2004;Ryberg et al, 2005), negative hormon receptor status (Samaan et al, 1981;Maki and Grossman, 2000) and HER2 overexpression (Gabos et al, 2006;Nam et al, 2008) are some of the reported risk factors for development of brain metastases. Survival after brain metastases is poor; it may be as short as 1-2 months for patients without treatment (DiStefano et al, 1979), while 8-10 months of survival times are reported for patients with systemic chemotherapy (Lee et al, 2008;Arslan et al, 2011;Kim et al, 2012). Although HER2 overexpression is a poor prognostic factor, the survival times of the HER2 positive patients with brain metastases treated with antiHER2 therapy (trastuzumab) are longer than the triple negative or HR(+) patients (Bendell et al, 2003;Kirsch et al, 2005;Nam et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Triple negative patients with brain metastases have the poorest prognosis compared to other biological subtypes . Median survival after central nervous system involvement in triple negative breast cancer (TNBC) patients are reported between 3.4-6.6 months (Eichler et al, 2008;Nam et al, 2008;Arslan et al, 2011). Due to the lack of hormon receptor and HER2 expression there is not any systemic treatment option except chemotherapy for TNBC.…”
Section: Discussionmentioning
confidence: 99%